Fostering culture resilience in housing for low-income earners - Haji Adenan, Rozia (2018)
Rapid urbanisation of cities surpassing development in rural areas, have provided the alternative for many living in village areas to migrate. The influx of migrants into cities is unprecedented and can be overwhelming, resulting in issues of affordable housing. This is further complicated by rural-to-urban migration that is creating the urban phenomenon of slums and informal settlements in cities. Cities have accepted to them as part of the urban fabric, allowing them to remain so long as they contribute to the city. Developing countries of comparatively larger population, with similar climate and cultural backgrounds, face common challenges often resulting in high-rise housing. Affordable formal housing areas are built to accommodate relocating slum dwellers. While this may be an answer to accommodating the increasing density of people in many cities, issues of cultural preservation, vernacular architecture conservation, social structures, environmental comfort and sense of community are often compromised by this urban solution. For the urban poor, it is these very aspects that they rely and depend on to survive the expensive living conditions. In spite of this, they continue living in cities. What is it that makes them tolerate their conditions? Can their resilience be the basis of sustainable housing community for low-income earners? Case studies conducted on residents in the Kampong Ayer and in small groups of selected formal housing on the mainland in Brunei Darussalam explored their culture and homes, and experiences on migration for answers. The findings of the studies showed that the affordability of the low-income residents in owning their own houses was their top priority, which influenced their decision to live in formal housing, or remain in informal settlements, as is often the case. Based on ‘leads’ from the findings, recommendations for improving the future of housing in Brunei Darussalam concluded the study. One of the recommendations was to build smaller houses for providing cost effective housing while considering ways of developing and encouraging a more community orientated society incorporated into the housing developments. For low-income earners, this does not compromise their culture because their family ties remain strong throughout.